2022
DOI: 10.1155/2022/3467773
|View full text |Cite|
|
Sign up to set email alerts
|

Innovation of Platform Economy Business Model Driven by BP Neural Network and Artificial Intelligence Technology

Abstract: In order to enhance the competitiveness of enterprises, how to evaluate and enhance the competitiveness of B2B e-commerce enterprises and promote the orderly and healthy development of B2B e-commerce industry are discussed. This paper puts forward the research on the innovation of platform economic business model driven by BP neural network and artificial intelligence technology. BP neural network is used to study and evaluate the competitiveness of B2B e-commerce companies. According to the B2B e-commerce com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Especially for the same candidate variables, after repeated iteration of machine learning, its prediction efficiency tends to be more robust, this is because variables in the "hidden layer" have been verified by multiple iterations, so better prediction efficiency can be obtained. [33,34] Therefore, the ANNM of the 5 machine learning prediction models included in this study is the best, whether in the internal training set or in the external verification queue, followed by RFM, which also confirms that the practical value of machine learning algorithms in AIS is beyond doubt.…”
Section: Discussionsupporting
confidence: 73%
“…Especially for the same candidate variables, after repeated iteration of machine learning, its prediction efficiency tends to be more robust, this is because variables in the "hidden layer" have been verified by multiple iterations, so better prediction efficiency can be obtained. [33,34] Therefore, the ANNM of the 5 machine learning prediction models included in this study is the best, whether in the internal training set or in the external verification queue, followed by RFM, which also confirms that the practical value of machine learning algorithms in AIS is beyond doubt.…”
Section: Discussionsupporting
confidence: 73%
“…This may be due to the fact that after correcting the weights of various neurons in the network, the network will be output in the forward propagation mode again, resulting in the error between the actual output value and the expected value, which can lead to a new round of weight correction. [ 44 , 45 ] Finally, the process of forward propagation and back propagation repeats until the network converges, and the interconnection weight and threshold value after the network converges are obtained, making the output result more robust.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%